Pregnancy after cardiac transplantation. Report of one case and review - Bordignon,Solange (2000)
A 14-year-old female patient became pregnant 6 years after heart transplantation. The pregnancy evolved uneventfully, and the newborn infant was healthy. Five months after delivery, the mother was in good condition with preserved ventricular function, and the baby had normal neuro-psychomotor development. Even though the case reported here was a success, pregnancy following cardiac transplantation is considered a high-risk condition and remains contraindicated.